MPFL Reconstruction in the Pediatric Population: Does Skeletal Maturity Matter?. Issue 7 (30th July 2021) - Hobson, Taylor; Mortensen, Alex; Tomasevich, Kelly; Adeyemi, Temitope; Aoki, Stephen; Quinlan, Noah
Objectives: Patellar instability requiring medial patellofemoral ligament reconstruction (MPFL) in the pediatric population poses a challenge in that the isometric point of femoral fixation (Schottle's point) is in close proximity to the distal physis. As a result, various alternative fixation techniques have been described to avoid physeal damage, however the consequences of this are unclear. Continued growth and altered graft mechanics in the growing child are areas of concern. The objective of the current study was to evaluate short to midterm outcomes, including redislocation rates, following MPFL reconstruction in skeletally immature versus mature pediatric patients. Methods: Patients under age 18 with recurrent patellar instability that underwent primary MPFL reconstruction by a single surgeon from 2013 to 2019 were identified using current procedural terminology (CPT) codes. Patients who were a minimum of 1 year from surgery were contacted to complete questionnaires. Questions pertained to knee pain and function, including International Knee Documentation Committee (IKDC) score, as well as further injury or surgery. Further data included chart and imaging review. Based on radiographic appearance of the distal physis, patients were placed into either the skeletally mature or immature cohort for comparison. Statistical analysis included chi-square, fisher's exact, and Mann-Whitney U tests. Significance was determined by p-value <0.05. Results: There were 103 primary MPFL reconstructions in 94 patients: 70 skeletally mature and 24 immature. As expected, the skeletally mature group was older (15.5 vs. 13.1 years). Skeletally immature patients had a higher incidence of trochlear dysplasia (88 vs. 63%, p=0.04). No other baseline differences were identified. Average follow-up was similar at 4.1 years for the mature group and 3.5 years in the immature. Skeletally immature patients were more likely to sustain a subsequent dislocation or any ipsilateral knee injury (15 vs. 3%, p=0.03; 35 vs. 16%, p=0.04 respectively). Skeletally immature patients underwent more revision instability procedures, which trended towards but did not reach significance (23 vs. 9%, p=0.06). No significant difference was observed in IKDC score (80 each), perceived percent of normal for that knee (85% each), frequency of instability events, current sport participation (42 vs. 31%), sport avoidance (46 vs. 35%), or subjective stiffness (38 vs. 41%). Visual analog scale pain scores for skeletally immature compared to mature patients were not different at rest, with activities of daily living, or with sport (0.9 vs. 0.8, 1.5 vs. 1.7, 2.5 vs. 3 respectively). Significantly fewer patients in the skeletally immature group were satisfied (79 vs. 97%, p<0.05) and would undergo the surgery again (68 vs. 100%, p<0.05). Conclusions: In pediatric patients undergoing MPFL reconstruction, both skeletally immature and mature patients have good and comparable outcomes. However, those that are skeletally immature are more likely to have a subsequent ipsilateral injury or dislocation. These patients are also less likely to be satisfied with their results. Of note, there was a higher incidence of trochlear dysplasia in skeletally immature patients which may predispose them to subsequent injury.